Antiplatelet Therapy in Neurointervention - Ma, Alice; Detaram, Harshil Dharamdasani; Steinfort, Brendan; Harrington, Tim; Nguyen, Thanh N.; Abdalkader, Mohamad; Siopis, George; Bath, Philip M.; Dhillon, Permesh Singh; Podlasek, Anna; Qureshi, Adnan I.; Qiu, Zhongming; Krishnan, Kailash (Seminars in Neurology, 2023)
The aim of this review is to provide an overview of the use of antiplatelet medication in neurointervention, with a focus on the clinical indications for antiplatelet use in both preventing and reducing platelet aggregation. This review will cover current antiplatelet medications, pharmacokinetics, and pharmacodynamics. We will provide an overview of different endovascular devices and discuss the antiplatelet regimes in neurointervention, highlighting gaps in evidence and scope for future studies.Two randomized controlled trials have evaluated antiplatelet use in the setting of acute large vessel occlusion stroke, with neither demonstrating benefit in their overall cohorts. Evidence on antiplatelet medication for both acute and elective stenting for acute stroke and treatment of cerebral aneurysms is currently based on large case series, and practice in neurointervention has increasingly utilized dual antiplatelet regimes with clopidogrel and second-line agents like prasugrel and ticagrelor. Clopidogrel function testing has an increasing role in neurointerventional procedures, particularly for high metal surface area stents such as the braided flow diverter type stents. Intravenous glycoprotein IIB/IIIA inhibitors have been utilized for both acute bridging and rescue therapy.Antiplatelet decision making is complex, and there are few randomized control trials to guide clinical practice. Comparative trials to guide decision making remain important in both the acute and elective settings. Standardised protocols incorporating platelet function testing may play a role in assisting decision making until more robust clinical evidence is available, particularly in the context of acute neurointerventional stenting for stroke and ruptured cerebral aneurysms.
Keywords: antiplatelet therapy; intracranial stenting; carotid stenting; stroke; aneurysms; mechanical thrombectomy